Genetic variability in soybean with resistance to cyst nematode and powdery mildew: impact of multi-parent crosses on recombination and genetic diversity - Muniz, F. R.S.; Souza, J. S. [UNESP]; Moitinho, A. C.R. [UNESP]; Torneli, I. M.B.; Unêda-Trevisoli, S. H. [UNESP]; Pfeiffer, T.; Di Mauro, A. O. [UNESP] (FapUNIFESP (SciELO), 2025)
The objective of this study was to analyze the genetic variability generated from two-way, four-way, and eight-way hybridizations in soybean, derived from parental lines contrasting in resistance to cyst nematode and powdery mildew. We assessed F2 populations using Simple Sequence Repeat (SSR) molecular markers located within the 50 cM region surrounding the Rmd (powdery mildew) and Rhg1 (cyst nematode) resistance genes. All markers were nonsignificant by chi-square test (P > 0.05), indicating that observed values align with the expected genotypic inheritance ratio in F2 populations (1:2:1). Lower polymorphism observed among parents explained the reduced recombination frequency in these populations. A higher mean crossover rate was observed in G4 (4.00) within linkage group G, and J8 (2.91) within linkage group J. In terms of the number of generations needed to form each population, crossover rates of 2.02 and 0.97 were found for G2 and J8, respectively. Recombination between alleles was present in some populations. Crosses involving a greater number of parents exhibited a higher frequency of crossovers, which positively impacts genetic variability. Therefore, the inclusion of more than two parents in hybridizations is recommended to enhance crossover frequency and genetic diversity. These findings provide valuable insights for breeding programs aiming to improve resistance in soybean, indicating that multi-parental crosses can be a strategic approach to increase genetic diversity and resilience against pathogens.